Childhood Trauma, Gaming, Drugs and Neurophysiology of Adolescent Vilolence - de Silva, Harendra (Faculty of Medicine, University of Colombo, 2020)
Youth violence as Physical, Emotional and Sexual violence and self-harm is considered. Norms domestic, peer societal and media violence get ...